Transfer Bioteknologi Pembuatan Tape Uli Daun Katuk Berbasis Protein Ikan Gabus sebagai Sumber Albumin (Booster Recovery Pasca Melahirkan) di Siawang Lumbis - Satriani, Gloria Ika; Abdiani, Ira Maya; Wulandari, Irene Caya (Jurnal PKM Manajemen Bisnis, 2025)
In Siawang Village, Lumbis District, Nunukan Regency, North Kalimantan, efforts to diversify food through biotechnology transfer to make snakehead fish protein-based katuk leaf uli tape as a source of albumin for postpartum mothers (booster recovery) can be an easy, cheap, solution. A simple, affordable way to overcome the difficulties of getting healthy daily nutrition during recovery. During postpartum recovery, problems such as wounds (such as cesarean scars or suturing wounds during expected delivery), constipation, and early initiation of breastfeeding (IMD) require attention and support from various roles, including medical personnel, family, and especially husbands. Mothers who have just given birth can include snakehead fish protein-based katuk leaf tape uli in their daily snacks. This snack has a unique and delicious taste and many essential health benefits for the body. The location of Siawang Village is far from the City Center, making the logistics of goods and services available in Siawang Village limited. Apart from that, the need for vitamin supplements, supplements and additional medicines is very low, especially in maintaining maternal health after giving birth. To prevent stunting or failure to thrive in toddlers due to chronic malnutrition, it is essential to ensure that mothers get enough nutrition during pregnancy, after giving birth, and during childcare. Community service activities (PKM) are conducted through lectures, training (direct practice), and discussions with the Siawang Village PKK Women mobilization group.